Perancangan UI/UX Aplikasi Penjualan Makanan berbasis Mobile pada UMKM di Kota Manado menggunakan metode Design Thinking - Jovianto Marcellino Dumalang; Chriestie E.J.C Montolalu; Dodisutarma Lapihu (Jurnal Ilmiah Informatika dan Ilmu Komputer (JIMA-ILKOM), 2023)
This research aims to create a User Interface (UI) and User Experience (UX) design so that people become easier to buy food at Culinary UMKMs using the Design Thinking method which has several stages, namely the Emphatize, Define, Ideate, Prototype, and Testing stages. The Design Thinking method is used to create solutions to solve problems felt by users. In conducting testing, the study used Usability Testing and tested 10 respondents who would provide an assessment through testing using the Single Ease Question which has a test result of 6.7 out of 7, and testing using the System Usability Scale which has a test result of 93 out of 100, which can be concluded that the UI / UX design of mobile-based food sales applications for MSMEs in the city of Manado can be used properly by respondents, and can provide solutions to existing problems.